Changes in ultra-processed food consumption during the first Italian lockdown following the COVID-19 pandemic and major correlates: results from two population-based cohorts - Bonaccio, Marialaura (Public Health Nutr, 2021)
OBJECTIVE: To evaluate changes in ultra-processed food (UPF) intake and its major correlates during the first Italian lockdown (9 March–3 May 2020). DESIGN: Retrospective observational study. SETTING: Italy. PARTICIPANTS: We analysed 2992 subjects (mean age 57·9 ± 15·3 years, 40·4 % men). Individual participant data were pooled from two retrospective cohorts: (1) The Moli-LOCK cohort consists of 1501 adults, a portion of the larger Moli-sani study (n 24 325; 2005–2010) who were administered a phone-based questionnaire to assess lifestyles and psychological factors during confinement and (2) the Analysis of Long Term Risk of Covid-19 Emergency is a web-based survey of 1491 individuals distributed throughout Italy who self-responded to the same questionnaire by using Google forms. UPF was defined according to NOVA classification based on degree of food processing. An UPF score was created by assigning 1 point to increased consumption, −1 to decreased and 0 point for unchanged intakes of nineteen food items, with higher values indicating an increase in UPF during confinement. RESULTS: Overall, 37·5 % of the population reported some increase in UPF (UPF score ≥1). Adults were more likely to decrease UPF (multivariable regression coefficient β = −1·94; 95 % CI −2·72, −1·17 for individuals aged >75 years as compared with 18–39 years) as did individuals from southern Italian regions as compared with Northern inhabitants (β = −1·32; 95 % CI −1·80, −0·84), while UPF lowering associated with increased exercise (β = −0·90; 95 % CI −1·46, −0·35) and weight loss (β = −1·05; 95 % CI −1·51, −0·59) during confinement. CONCLUSIONS: During the first Italian lockdown, about 40 % of our population switched to unfavourable eating as reflected by increased UPF intake and this may have long-term effects for health.